(untitled) (London, 1996)
This book provides an analysis of case studies of secondary classrooms which compared students thought to be good classroom managers with those thought to be poor managers. The book also reports the findings of questionnaires which asked pupils how they perceive effective classroom management, and asked teachers at different stages in their careers how they perceive their job
Keywords: Education,Study,Teaching; method of